This question was previously asked in

EKT Computer Science Previous Year Paper 3 : 01/2015 Shift

Option 1 : 1/4

EKT ME Full Test 1

2044

50 Questions
150 Marks
45 Mins

__Concept:__

**P(A****⋂****B) = P(A) + P(B) - P(A****⋃****B)**

\(P\left( {\frac{A}{B}} \right) = \frac{{P\left( {A\bigcap B} \right)}}{{P\left( B \right)}}\)

__Calculation:__

__Given:__

P(A) = 1/4, P(B) = 1/3, P(A⋃B) = 1/2

**P(A****⋂****B) = P(A) + P(B) - P(A****⋃****B)**

**\(P\left( {A\bigcap B} \right) = \frac{1}{4} + \frac{1}{3} - \frac{1}{2} = \frac{{3 + 4 - 6}}{{12}} = \frac{1}{{12}}\)**

Now

\(P\left( {\frac{A}{B}} \right) = \frac{{P\left( {A\bigcap B} \right)}}{{P\left( B \right)}}\)

\(P\left( {\frac{A}{B}} \right) = \frac{{\frac{1}{{12}}}}{{\frac{1}{3}}} = \frac{3}{{12}} = \frac{1}{4}\)